Competing hydrogen-bond donors: phenols vs. cyanooximes - Aakeröy, Christer B.; Epa, Kanishka N.; Forbes, Safiyyah; Desper, John (My University, 2013)
Based on a systematic structural study of co-crystals of a ditopic probe molecule, (Z)-N,4-dihydroxybenzimidoyl cyanide, decorated with an –OH group and a cyanooxime moiety, it has been shown that in a competitive molecular recognition event, the former is the better hydrogen-bond donor. This structural behaviour is reflected by calculated electrostatic potential surfaces of the competing donors, which highlights that electrostatic charge can offer a reliable tool for predicting primary hydrogen-bond preferences.
Keywords: Hydrogen-bond donors; Phenols; Cyanooximes